Perceptions of primigravida and their husbands regarding the need for maternal-fetal attachment stimulation - Purwati, Yuni; Pramono, Noor; Hakimi, Mohammad; Sudarmiati, Sari; Anggorowati, Anggorowati (International Journal of Public Health Science (IJPHS), 2024)
Prenatal class programs for primigravidas are important to improve fetal care behavior and reduce infant mortality. In prenatal classes, there is no maternal-fetal attachment stimulation education program which is important for improving maternal-fetal attachment and fetal well-being. The perceptions of pregnant women and their husbands regarding knowledge and experience of pregnancy as well as maternal-fetal attachment (MFA) stimulation are important for assessing the need for MFA educational materials. The research aimed to examine the perceptions of primigravidas and their husbands regarding pregnancy and MFA stimulation. Exploratory descriptive qualitative study method. Data were collected using in-depth interviews with 10 primigravidas and their husbands at the Community Health Center in Bantul, Yogyakarta, Indonesia, using an interview guide. Data analysis by condensing data, presenting data, and drawing conclusions, verbatim results of interviews are presented in coding, found categories, and themes. Four themes were produced: knowledge of pregnancy and fetal growth and development; concept of maternal-fetal attachment skills; management of pregnancy emotional management; and husband's support. The conclusion of this theme's findings underlies the development of maternal-fetal attachment educational materials in prenatal classes to prepare mothers for their role, and improve MFA and maternal-fetal health.